Comparing the effect of progressive muscle relaxation exercise and support group therapy on the happiness of nursing students: A randomized clinical trial study - Sanaz Bostani; Masoume Rambod; Paricheher Sabaghzadeh Irani; Camellia Torabizadeh (Elsevier, 2020)
Background: Some nursing students might experience lower and median levels of happiness; hence, providing some interventions would be crucial for them. Objective: This study aimed to compare the effects of Progressive Muscle Relaxation (PMR) exercise and support group therapy on happiness amongst nursing students. Design: This was a randomized controlled trial study. Participants: In this study, 150 nursing students participated. They were selected from nursing and midwifery school of Shiraz University of Medical Sciences. Methods: 150 nursing students were divided into three groups (PMR exercise (n = 50), support group therapy (n = 50), and control (n = 50)). PMR exercise and support group therapy were carried out over five consecutive 45-minute sessions per week for 50 participants in groups of 10. Oxford Happiness Inventory was used before and after the interventions. In order to compare the mean score of happiness between two and three groups, t-test, and ANCOVA were used, respectively. Results: After the intervention, the mean scores of happiness were 55.26 (SD = 16.26), 35.16 (SD = 12.69), and 34.22 (SD = 11.83) in the PMR exercise, support group therapy, and control groups, respectively. The results indicated a significant difference amongst the three groups regarding happiness after the intervention (p < 0.05). A significant difference was observed between the PMR exercise and the control group regarding happiness (p < 0.05). In addition, the mean score of happiness was significantly higher in the PMR exercise group compared to the support group therapy after the intervention (p < 0.05). In the PMR exercise group, a significant difference was found regarding the mean change of students' happiness before and after the intervention (t = -4.29, p < 0.001). Conclusion: Considering the positive effects of PMR exercise and support group therapy in increasing nursing students' happiness, educational authorities and educators are recommended to use these therapies during the course of nursing' Bachelor's degree to increase happiness within students and positive outlooks amongst groups.